Žurnalistikos istorijos ir teorijos klausimai “Aušroje” - Raguotis, Bronius (Knygotyra, 1995)
The literary magazine “Aušra” (Dawn) (1883–1886) was enormously significant for the Lithuanian journalism. In “Aušra” questions concerning historical and theoretical problems of national journalism came to the foreground.“Aušra” and it’s editorial staff concentrated on the analysis of journalistic forms, history of the media. Articles, publications are very important as reliable source of information, now.“Aušra” had a great influence on the researchers of journalistic terms. Many of them are used till our days. Many authors, including J. Andziulaitis-Kalnėnas, J. Basanavičius, J. Mačys-Kėkštas, S. Raila, J. Šliūpas, were interested in these problems.“Aušra” played a great role in formation of Lithuanian national journalism.